Non-linear thermal resistance model for the simulation of high power GaN-based devices. (29th March 2021) - García-Sánchez, S; Íñiguez-de-la-Torre, I; Pérez, S; Ranjan, K; Agrawal, M; Lingaparthi, R; Nethaji, D; Radhakrishnan, K; Arulkumaran, S; Ng, G I; González, T; Mateos, J
Abstract: We report on the modeling of self-heating in GaN-based devices. While a constant thermal resistance is able to account for the self-heating effects at low power, the decrease of the thermal conductance of semiconductors when the lattice temperature increases, makes necessary the use of temperature dependent thermal resistance models. Moreover, in order to correctly account for the steep increase of the thermal resistance of GaN devices at high temperature, where commonly used models fail, we propose a non-linear model which, included in an electro-thermal Monte Carlo simulator, is able to reproduce the strongly non-linear behavior of the thermal resistance observed in experiments at high DC power levels. The accuracy of the proposed non-linear thermal resistance model has been confirmed by means of the comparison with pulsed and DC measurements made in devices specifically fabricated on doped GaN, able to reach DC power levels above 150 W mm −1 at biases below 30 V.